Principal Leadership and Academic Service Management in Indonesian Junior High Schools: Challenges and Opportunities - Muthahharah Thahir; Ananda Rachmaniar; Cucun Sunaengsih; Widiawati Widiawati (Journal of Education and Teaching (JET), 2025)
This study aims to determine the leadership capacity of school principals in improving the quality of academic service management. A mixed-method approach was employed, involving both public and private junior high schools in Gowa Regency, South Sulawesi, Indonesia, with a total population of 523 teachers. Using Slovin’s formula, a sample size of 231 teachers was selected. Data were analyzed descriptively using mean scores to assess various leadership capacity indicators. The findings indicate that school principals in SMP/MTs in Gowa Regency, South Sulawesi, Indonesia demonstrate strong leadership capacity in enhancing the management of academic service quality, reflected by an achievement level of 80.52%, which falls into the “good” category. This capacity is evidenced by their ability to make participatory decisions, communicate and coordinate effectively, and motivate school members.However, communication remains an area for improvement, as current practices are often top-down, limiting meaningful feedback and engagement from teachers and staff. The study recommends targeted capacity-building programs-such as leadership workshops, peer mentoring, and communication training-facilitated either through self-initiated development or with support from the regional Department of Education.